Regulatory Frameworks for Dam Safety : A Comparative Study - Bradlow, Daniel D.; Palmieri, Alessandro; Salman, Salman M. A. (Washington, DC: World Bank, 2013)
This study is a comparative assessment of the regulatory frameworks applicable to dam safety in 22 countries. It is divided into three parts. The first part is a description of the dam safety regulatory framework in each of the 22 countries. The countries were selected based on the availability of information about their dam safety regulatory frameworks. The second part of the study is a comparative analysis of these regulatory frameworks. The analysis attempts to highlight the main similarities and differences in the approaches adopted by the countries discussed in the first part of the study. The third part offers recommendations on what a regulatory framework for dam safety should contain. It lists essential elemetns that should be included in all dam safety regulatory frameworks, as well as elemetns that would be desirable to include in such regulatory frameworks. This part also identifies and discusses a number of emerging trends in dam safety. In tis connection, this part of the study can be seen as providing a tool kit that can be used in formulating a regulatory framework for dam safety. This study has seven appendices. Appendix iv contains a dam safety statute; appendix V is a dam safety regulation; and appendix vi is a sample operations, maintenance, and surveillance manual.